Journal of Synchrotron Radiation: open call for new Main Editor to join leadership team - Office, Editorial (Journal of synchrotron radiation, 2020)
An open call is made for a new Main Editor for Journal of Synchrotron Radiation. An open call is made for a new Main Editor for Journal of Synchrotron Radiation.